EXTERNAL AND INTERNAL SECRETION OF THE PANCREAS IN EXPERIMENTAL PANCREATITIS - Sysa, Aliaksei Ryhor (Journal of the Belarusian State University. Ecology, 2023)
In experiments on white rats with L-arginine-induced experimental pancreatitis, the histostructure of the pancreas, activity of α-amylase in the tissue of the pancreas and intestinal chyme, the content of glucose, C-peptide and the activity of α-amylase in the blood serum were determined. It was revealed that the destruction of the acini was also accompanied by a change in the structure and size of the pancreatic islets of the organ. In addition, an increase in the activity of α-amylase in the bloodstream and a sharp decrease in the secretion of the enzyme into the cavity of the small intestine were accompanied by an increase in the level of glucose in the blood and a decrease in the content of C-peptide in hemocirculation. Consequently, experimental pancreatitis can be the cause of dysfunction of the endocrine apparatus of the pancreas